Namibia : 2013 Article IV Consultation-Staff Report; Press Release. (IMF Staff Country Reports; Country Report, 2014)
This 2013 Article IV consultation highlights Namibia's positive growth record over the years, which has raised overall incomes and led to positive economic outcomes. However, growth has not translated into sufficient job creation, and unemployment and income inequality are persistently high. Real GDP growth is expected to moderate to 4 percent in 2013 from 5 percent in 2012 reflecting weak global demand for exports partially offset by solid growth in domestic demand. Given the uncertain external environment, the IMF staff recommends that the authorities pursue 'growth-friendly' fiscal consolidation, reining in unproductive current spending while protecting growth-promoting capital spending. The IMF staff also welcomes efforts by the government to look into ways to steer a gradual reduction of the wage bill, which would improve labor market outcomes.